ISLAMIC FINANCIAL LITERACY IN THE BIMWIN MODULE: AN URGENT NEED IN THE ERA OF DIGITAL CONSUMERISM - Ahmad Hanafi; Khairil Anwar (JURNAL PROFIT, 2025)
The digital era has transformed financial behavior and consumption patterns of young Muslim couples preparing for marriage. The proliferation of digital financial services such as paylater, online lending, and fintech investment platforms presents significant challenges for family financial management based on Islamic values. In response, the Ministry of Religious Affairs of Indonesia has integrated Islamic financial literacy content into the Bimbingan Perkawinan (Bimwin) program. However, analysis reveals that the current content remains normative and lacks contextual adaptation to the digital financial ecosystem faced by Millennials and Gen Z. This study employs a qualitative-descriptive approach using document analysis and literature review to identify gaps between normative teachings and practical application. The findings highlight that Bimwin participants face substantial challenges in translating Islamic financial principles into daily financial decision-making within digital environments. The study proposes comprehensive strategies, including contextual learning through digital financial case studies, simulation-based training, facilitator capacity-building, and multi-stakeholder collaboration. Strengthening Islamic financial literacy through these strategies can equip young Muslim families with critical skills to navigate the digital economy ethically and sustainably in accordance with maqashid sharia principles.